Investigation of Indoor Thermal Environments in a Two-Story Corner Terrace House in Malaysia - Wai Tuck, Ng; Ahmad Zaki, Sheikh; Hagishima, Aya; Bahadur Rijal, Hom; Azuan Zakaria, Mohd; Yakub, Fitri (KnE Social Sciences, 2019)
An effective passive cooling strategy is essential for reducing energy consumption in a residential building without ignoring thermal comfort. Therefore, a field measurement on the thermal performance of a corner terrace house in Kuala Lumpur was conducted to reveal the effectiveness of free running (FR) with four different approaches – no ventilation, full ventilation, day ventilation, and night ventilation. The measurement was done for all bedrooms and family area on the first floor. Also, mixed mode (MM) consisting of natural ventilation, mechanical ventilation with ceiling fan, and cooling with an air-conditioner that represents the actual condition of this house was also measured at living and dining area on the ground floor for comparison. The results reveal that FR from all approaches recorded a mean indoor air temperature of approximately 31 ∘C. The actual thermal condition of the house with MM on the ground floor was recorded at 30 ∘C, 1 ∘C lower than FR approach on the first floor. When compared with relevant international standards on predicting indoor comfort temperature based on outdoor temperature, FR was approximately 5 ∘C higher than predicted temperature based on American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) Standard 55 (2017), 3.4 ∘C higher than European Standard EN15251 and 1.5 ∘C higher than adaptive thermal comfort equation (ACE) for hot-humid climate. In comparison, MM performed better and was closer to relevant international standards, especially ACE for the hot-humid climate. As a conclusion, FR is not suitable for a hot-humid climate such as Malaysia to achieve a comfortable indoor thermal environment without any assisted ventilation use in MM.